Adaptive synchronization of multi-agent systems with resilience to communication link faults - Chen, Ci (2021)
The resilience of multi-agent systems (MAS) measures the capability of recovering the cooperative performance after experiencing faults or uncertainties. In this paper, we seek the improvement of the synchronization resilience for MAS by means of addressing unknown faults on communication links. To this end, we first transform the resilient control problem into designing distributed state observers. In addition, we show that the proposed state observers are resilient to communication link faults. Finally, we provide the main result of this paper as a synchronization protocol for MAS even in the presence of communication link faults.